Peran Media Sosial dalam Transformasi Proses Pembelajaran dan Interaksi Sosial pada Generasi Digital - Basuni, Abas Firdaus; Ningsih, Tutuk (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – Globalization and the advancement of digital technology have transformed various aspects of life, including education and socialization among students. This study aims to analyze the impact of social media on students' cognitive and social aspects.Method – The study adopts a library research method, reviewing academic literature to explore phenomena such as digital addiction, reduced learning concentration, changes in interpersonal interaction, and challenges in character-building in the digital era. Findings – The findings reveal that social media offers benefits such as easy access to information and the development of online learning communities. However, it also poses negative impacts, including digital addiction, decreased learning concentration, plagiarism, reduced empathy, and social pressures that affect students' mental health. In the cognitive domain, social media addiction disrupts brain function, diminishes critical thinking skills, and weakens learning motivation. In the social domain, the shift to virtual interactions reduces emotional engagement, weakens interpersonal communication skills, and leads to social isolation and cyberbullying. Furthermore, exposure to idealized standards on social media triggers anxiety, depression, and other mental health challenges. Research Implications – This study underscores the need for digital literacy programs to help students use social media wisely and integrate it into educational processes to maximize its benefits. Schools are encouraged to adopt a holistic approach to develop students' face-to-face communication skills, while collaboration among teachers, parents, and students is essential for managing social media use effectively. This study provides insights for educators, parents, and policymakers to understand the impacts of social media and optimize its potential in education.